The Development of Read Riddle Games to Improve Students' Reading Interest - Lira Aulia Hakim; Pahmi Pahmi; Prih Febtiningsih (ELT-Lectura, 2023)
Reading is an important aspect of the Senior High School curriculum, especially in areas where languages were integrated. The curriculum focuses on teaching grammatical awareness, structure, and reading comprehension to help students progress from basic knowledge to higher levels of language use. This study aims to discover the students’ outcomes by developing learning media using Google Site called "Read Riddle Games" for grade X SMA Negeri 2 Pekanbaru. The subject in this study is X MIPA 4 class in 2022/2023 academic year. This study used ADDIE (Analysis, Design, Development, Implementation and Evaluation) as the methodology to design and develop a learning media product. The learning media were validated by material expert, media expert and trial with the students. The researcher used questionnaires as the instruments in this study. The analysis of trial with the students using questionnaire with Gain Classification revealed a significant improvement in students' interest in reading after the enforce of the developed learning media with an average of 71% increase in students’ interest in reading. The development of the "Read Riddle Games" learning media has demonstrated high feasibility both in terms of material aspects and media aspects. This finding show that the learning media developed can be used to enhance students' interest in reading, thus contributing to a more effective educational experience.